SOSIALISASI DAN PELATIHAN PENGELOLAAN SAMPAH DENGAN KONSEP ZERO WASTE LIFESTYLE DI KELURAHAN SELONG - Hidayati, Siti Nur Isnaini; Soliha, Mar’atun; Wahida, Laelatul; Iswara, Muhammad Apria; Alundari, Baiq Trinadia; Wanti, Joice Sari; Ana, Susmaini; Sutawijaya, I Gede Pasek (Jurnal Wicara, 2023)
Community Service Activities (KKN) are a form of community service carried out by students, in the context of implementing higher education's three dharma. Garbage is a crucial problem, even including a cultural problem because the impact it creates will disrupt all aspects of life. The principle of zero waste (free waste) in general is an integrated waste management system with the zero waste concept applying the 3R principles (reduce, reuse, recycle), 4R or 5R. The phenomenon of waste in the Selong sub-district has become an urgent problem and the most appropriate solution must be found to overcome it. This activity aims to help the community understand the procedures for managing waste and developing the concept of zero waste in Selong Village. The Community Service Program (KKN) will be held from 20 December 2022 to 10 February 2023, which is located in Selong Village, Selong District, East Lombok Regency. The stages of activities carried out in the implementation of KKN are as follows; Field Survey, Socialization of Waste Management & Zero Waste Lifestyle Concept, Compost Making Training, Craft & Ecobrick Making Training, Activity Evaluation. Waste management socialization and training activities with the concept of zero waste lifestyle in Selong Sub-District are carried out starting from the first week to the last week of January with a series of activities, namely socialization, training on making compost, training on making handicrafts. The socialization activity aims to provide an understanding of waste management procedures, especially organic and inorganic waste and its utilization into new products that have economic value.